A study on the relationship between intellectual capital and business performance in the engineering consulting industry: A path analysis - Huang, Chung-Fah; Hsueh, Sung-Lin (Journal of Civil Engineering and Management, 2007)
Engineering consulting firms, like other knowledge‐based enterprises, take intellectual capital as their most important asset embedded in the organisation. This research aims to analyse the correlation between intellectual capital and business performance. The questionnaire was sent to all Taiwan’s engineering consulting firms, and 101 copies were collected. It was found that, among these engineering consulting firms, the structural capital and relational capital show better performance, while human capital has poorer performance. This is especially true for staff education and training. This indicates that there is still room for improving human resource management by engineering consulting firms. It is observed by path analysis that, among the three dimensions of engineering consulting firms’ intellectual capital, the human capital has a great influence on structural capital and relational capital. However, only relational capital has a direct influence on business performance. Human capital has an influence upon the business performance via the relational capital. Intelektinio kapitalo ir verslo vykdymo konsultacinėje inžinerijos pramonėje santykis: daugiafaktorinė regresinė analizė Santrauka. Inžinerinės konsultacinės įmonės, kaip ir kitos žiniomis grįstos organizacijos, intelektinį kapitalą laiko svarbiausiu turtu. Šio tyrimo tikslas yra nustatyti intelektinio kapitalo ir verslo vykdymo koreliaciją. Anketa buvo išsiųsta visoms Taivano inžinerinėms konsultacinėms įmonėms, atsakė 101 respondentas. Buvo nustatyta, kad struktūrinis ir santykinis šių inžinerinių konsultacinių įmonių kapitalas parodė geresnių rezultatų nei žmogiškasis kapitalas. Ši tiesa atsispindi ugdant darbuotojus ir juos mokant. Tai parodo, kad inžinerinėse konsultacinėse įmonėse vis dar galima gerinti žmogiškųjų išteklių valdymą. Iš atliktos daugiafaktorinės regresinės analizės buvo matyti, kad tarp inžinerinių konsultacinių įmonių intelektinis ir žmogiškasis kapitalas turi didelę įtaką struktūriniam ir santykiniam kapitalui. Tačiau tik santykinis kapitalas turi tiesioginį poveikį verslui. Žmogiškasis kapitalas daro poveikį verslo vykdymui per santykinį kapitalą. Reikšminiai žodžiai: inžinerinė konsultacija, intelektinis kapitalas, verslo vykdymas, daugiafaktorinė regresinė analizė. First Published Online: 14 Oct 2010